Release of muscle alpha-actin into serum after intensive exercise - Martinez-Amat, A.; Marchal, J. A.; Prados, J.; Hita, F.; Rodriguez-Serrano, F.; Boulaiz, H.; Martin, I.; Melguizo, C.; Caba, O.; Velez, C.; Ortiz, R.; Rama, A. R.; et al. (Biology of Sport, 2010)
Purpose: To study the effects of high-level matches on serum alpha actin and other muscle damage markers in teams of rugby and handball players. Methods: Blood samples were drawn from 23 sportsmen: 13 rugby players and 10 handball players. One sample was drawn with the player at rest before the match and one immediately after the match. Immunoassays were used to determine troponin I, troponin T, LDH, and myoglobin concentrations. Western blot and densitometry were used to measure alpha-actin concentrations. Muscle injury was defined by a total CK value of > 500 IU/L (Rosalki method). Results: Mean pre- and post-match serum alpha-actin values were, respectively, 7.16 and 26.47 mikro-g/ml in the handball group and 1.24 and 20.04 mikro-g/ml in the rugby team. CPK, LDH and myoglobin but not troponin 1 levels also significantly differed between these time points. According to these results, large amounts of alpha-actin are released into peripheral blood immediately after intense physical effort. Possible cross-interference between skeletal and cardiac muscle damage can be discriminated by the combined use of alpha-actin and troponin I. Conclusion: The significant increase in alpha-actin after a high-level match may be a reliable marker for the early diagnosis and hence more effective treatment of muscle injury.